2018
DOI: 10.3390/ma11071137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Particle Shape on Sintering Behavior and Compressive Strength of Porous Alumina

Abstract: Alumina particles with different shapes, such as sphere, rod, and disk, were examined for the sintering behavior and compressive strength of partially sintered porous alumina. While both the spherical and disk-like particles were packed well to the relative density of 61.2–62.3%, the packing density of rod-like particles was only 33.5%. The sintering rate of alumina particles increased in the order of disk < rod < sphere. The compressive strength of sintered porous alumina was higher for the spherical particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…For this modified surface, the average E value was approximately 359.3 GPa on the ceramic surface layer, followed by 278.0 GPa on the diffused phase and 200.4 GPa on the steel substrate. It can be stated that the obtained Young's modulus for the multi-phase ceramic layer was a value similar to the alumina-like (Al 2 O 3 ) properties, around 360.0 GPa [23]. The selective diffusion layer formed a composite characteristic between E values of alumina and steel, whereas on the main steel substrate, it remained unchanged for approximately 200.0 GPa, in agreement with the typical Young's modulus ranges of steel.…”
Section: Resultssupporting
confidence: 73%
“…For this modified surface, the average E value was approximately 359.3 GPa on the ceramic surface layer, followed by 278.0 GPa on the diffused phase and 200.4 GPa on the steel substrate. It can be stated that the obtained Young's modulus for the multi-phase ceramic layer was a value similar to the alumina-like (Al 2 O 3 ) properties, around 360.0 GPa [23]. The selective diffusion layer formed a composite characteristic between E values of alumina and steel, whereas on the main steel substrate, it remained unchanged for approximately 200.0 GPa, in agreement with the typical Young's modulus ranges of steel.…”
Section: Resultssupporting
confidence: 73%
“…The NiTi powder particles have a shape factor close to 1 ( Figure 2 ) [ 19 , 20 ]. The particle size was d 50 = 22.1 µm ( Figure 3 ), which is typical of powder particles used in direct additive processes (i.e., SLM and electron beam melting (EBM)), but they could contribute to problems during sintering in indirect processes.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of clustering and interfacial debonding of particles on the mechanical properties of sintered materials were the topic of majority of the prior studies. Number of studies confirmed the fact that less porosity in the material microstructure leads to higher material stiffness and strength, while an irregular shape of pores strongly influences the material fracture toughness and strength [3][4][5][6][7]. But sometimes porosity is quite necessary e.g.…”
Section: Introductionmentioning
confidence: 94%